A Review of the Legal Aspects of Regulations Governing the Destruction of Electronic Medical Records in Indonesia - lakhmudien; Qonita Ulfiana; Rano I Sudra; Irwan Syah; Edi Pranoto; Sigit Irianto (Journal of Innovative and Creativity (Joecy), 2026)
The digital transformation of healthcare services has accelerated the implementation of Electronic Medical Records (EMRs) in Indonesia to improve healthcare quality, operational efficiency, and the integration of health information systems. This transformation has also generated legal challenges, particularly concerning the regulation of Electronic Medical Record destruction following the expiration of the legally prescribed retention period. This study aims to analyze the legal framework governing the destruction of Electronic Medical Records in Indonesia. The research employed a normative legal research method using a statutory approach and a conceptual approach. Primary legal materials consisted of Law Number 17 of 2023 on Health and Minister of Health Regulation Number 24 of 2022 on Medical Records, while secondary legal materials were obtained from legislation, legal literature, and relevant scientific journals. The collected data were analyzed qualitatively using Gustav Radbruch's theory of legal certainty as the analytical framework. The findings indicate that Law Number 17 of 2023 recognizes the destruction of health data and information through Article 349; however, the provision remains general and does not regulate the operational mechanisms for implementing data destruction. Minister of Health Regulation Number 24 of 2022 establishes a minimum retention period of 25 years from the patient's last visit for Electronic Medical Records but does not provide procedures governing the destruction of records after the retention period expires, including destruction procedures, secure deletion standards, authorized officials, documentation, audit mechanisms, and supervisory procedures. This condition demonstrates the existence of a normative gap that has resulted in the absence of legal certainty for healthcare facilities in implementing the destruction of Electronic Medical Records. This study recommends harmonizing the existing regulatory framework through the enactment of comprehensive technical regulations governing the destruction of Electronic Medical Records to ensure legal certainty, strengthen the protection of health data, and enhance accountability in health information system governance.